Study on the characteristics and properties of composites based on PLA/TiO2 and thermoplastic starch - Mai, Tran Thi; Thu Trang, Nguyen Thi; Thuy Chinh, Nguyen; Tham, Do Quang; Trung, Tran Huu; Hoang, Thai (Vietnam Journal of Science and Technology, 2025)
The purpose of this study is to fabricate composites based on poly(lactic acid) (PLA), thermoplastic starch (TPS) and TiO2 nanoparticles (n-TiO2), and to investigate the effects of TiO2 on the interface compatibility of TPS and PLA. The FTIR spectra confirmed that the interfacial interaction between the components is the formation of hydrogen bonding between TiO2 and PLA/TPS matrix (Ti-O-C bond). The results indicated that the tensile properties of PLA/TPS blends were strongly influenced by the PLA/TPS ratio which decreased with increasing TPS content. Besides, the tensile strength of the composites was improved in the presence of n-TiO2 particles due to the high crystallinity of the PLA/TPS/n-TiO2 composites (with an n-TiO2 content of 1 wt.%) in comparison with the PLA/TPS blends as shown in DSC and XRD analysis. The TGA results also indicated that the thermal stability of the PLA/TPS/n-TiO2 composites was improved with the addition of TiO2 nanoparticles. Finally, SEM images indicated that TiO2 nanoparticles were well dispersed in the PLA/TPS matrix at low TiO2 content. At high TiO2 content (2 wt.%) it caused agglomeration into clusters which reduced the properties of the composites.